2020
DOI: 10.3390/ijerph17082860
|View full text |Cite
|
Sign up to set email alerts
|

Development and Psychometric Properties of a Questionnaire Assessing Self-Reported Generic Health Literacy in Adolescence

Abstract: Health literacy is a promising approach to promoting health and preventing disease among children and adolescents. Promoting health literacy in early stages of life could contribute to reducing health inequalities. However, it is difficult to identify concrete needs for action as there are few age-adjusted measures to assess generic health literacy in young people. Our aim was to develop a multidimensional measure of health literacy in German to assess generic health literacy among 14- to 17-year-old adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 73 publications
2
37
0
3
Order By: Relevance
“…Rathmann and colleagues [74] consider the organizational health literacy in facilities for people with disabilities in their pilot mixed-methods study: "Organisational Health Literacy in Facilities for People with Disabilities: First Results of an Explorative Qualitative and Quantitative Study". Domanska et al [75] provide new evidence around self-reported health literacy in adolescence in "Development and Psychometric Properties of a Questionnaire Assessing Self-Reported Generic Health Literacy in Adolescence".…”
Section: Organizational Level: Schools Students and Adolescentsmentioning
confidence: 99%
“…Rathmann and colleagues [74] consider the organizational health literacy in facilities for people with disabilities in their pilot mixed-methods study: "Organisational Health Literacy in Facilities for People with Disabilities: First Results of an Explorative Qualitative and Quantitative Study". Domanska et al [75] provide new evidence around self-reported health literacy in adolescence in "Development and Psychometric Properties of a Questionnaire Assessing Self-Reported Generic Health Literacy in Adolescence".…”
Section: Organizational Level: Schools Students and Adolescentsmentioning
confidence: 99%
“…In anderen Studien, die mittels HLS-EU-Q selbstberichtete GK erfassen, zeigt sich, dass bei 15- [19] sowie 14-bis 17-Jährigen [7] selbstberichtete und funktionale GK korrelieren, was auch bei Erwachsenen beobachtet wurde [11].…”
Section: Dimensionen Der Gesundheitskompetenzunclassified
“…Finally, a random sample of adolescents per birth cohort was drawn based on calculations which consider the community size and sample points (first birth cohort: 01.09. [39]. The response rate (17.3%) following the first batch of study invitations (n = 500) was lower than expected.…”
Section: Sampling Strategiesmentioning
confidence: 66%
“…In pretest, the MOHLAA-Q scales yielded acceptable validity indicators. The reliability coefficients (Cronbach's α) of the scales reported were 0.54 to 0.77 [39]. The psychometric properties of the MOHLAA-Q indicated that the instrument can be used to assess different dimensions of health literacy.…”
Section: Measurementsmentioning
confidence: 94%
See 1 more Smart Citation